Sinoatrial node heterogeneity and fibroblasts increase atrial driving capability in a two-dimensional human computational model - Ricci, Eugenio; Mazhar, Fazeelat; Marzolla, Moreno; Severi, Stefano; Bartolucci, Chiara (Frontiers in Physiology, 2024)
Cardiac pacemaking remains an unsolved matter under many points of view. Extensive experimental and computational research has been performed to describe sinoatrial physiology across different scales, from the molecular to the clinical level. Nevertheless, how the heartbeat arises inside the sinoatrial node and propagates to the working myocardium is, at present, not fully understood. This work aims at providing quantitative information about this fascinating phenomenon, especially regarding the contribution of cellular heterogeneity and fibroblasts to sinoatrial node automaticity and atrial driving. This is achieved by developing a bi-dimensional computational model of human right atrial tissue including the sinoatrial node. State-of-the-art knowledge of anatomical and physiological aspects was adopted during the design of the baseline tissue model. The novelty of this study is the presence of cellular heterogeneity and fibroblasts inside the sinoatrial node to investigate how they tune the robustness of stimulus formation and conduction under different conditions (baseline, ionic current blocks, autonomic modulation, external high frequency pacing). The simulations show that both heterogeneity and fibroblasts significantly increase the safety factor for conduction by more than 10% in almost all the conditions tested and shorten the sinus node recovery time after overdrive suppression up to 60%. In the human model, especially in challenging conditions, fibroblasts help the heterogeneous myocytes to synchronize their rate (e.g., -82% in σCL under 25 nM acetylcholine administration) and to capture the atrium (with 25% L-type calcium current block). However, anatomical and gap junctional coupling aspects remain the most important model parameters to allow an effective atrial excitation. In conclusion, despite the limitations of the model, this work suggests a quantitative explanation to the astonishing overall heterogeneity shown by the sinoatrial node.